Faktor-Faktor yang Mempengaruhi Pajak Daerah Kota Semarang - Firman Bayu Aji; Nugroho SBM (Universitas Diponegoro, 2021)
Taxes are a source of regional income. Semarang City in terms of PAD has tax revenues that are still volatile. Judging from the existing tax potential, the City of Semarang has quite good potential but has not been explored effectively and efficiently. This study aims to analyze the factors that affect Semarang City local taxes with the independent variables of PDRB, inflation, number of industries and population density. The data used in this research is secondary data. The analysis model used is multiple linear regression analysis. Multiple linear regression analysis using the classical assumption test includes normality test, multicollinearity test, autocoleration test, heteroscedasticity test, and hypothesis testing through the F test, t test and coefficient of determination (R2). The results of the analysis of this study indicate that the GRDP and inflation variables have a significant positive effect, while the number of industries and population density variables have a positive and insignificant effect. The analysis of the F test results shows that the variables of GRDP, inflation, population density and the number of visitors to tourism objects simultaneously influence local tax revenues. The Adjusted R square value of 87 percent of the independent variable can affect government revenue, while 13 percent of local tax revenue is influenced by variables other than the variables used in the study.